Molecular detection and characterization of tick-borne hemopathogens in stray dogs in Malaysia - Mohammed, Konto (2016)
Tick-borne hemopathogens like Babesia, Ehrlichia, Anaplasma and Hepatozoon species pose significant health threats to dogs worldwide. Southeast Asia is one of the few regions of the world with inadequate records concerning vector-borne diseases of dogs and cats, yet it happens to be among the most heavily populated with stray dogs and cats and a climate that is ideal for the tick vectors. In an attempt to achieve a comprehensive scenario for Malaysia, molecular screening and characterization of five major canine tick-borne hemopathogens (namely: Anaplasma platys, Babesia vogeli, Babesia gibsoni, Ehrlichia canis and Hepatozoon canis) was carried out. West (Peninsular) Malaysia was divided into four quadrants; North, East, South and West Peninsular, while the East (Island) Malaysia was divided into North and South. Eight out of the 12 States of Malaysia were selected for this study which comprises: Penang, Kedah, Pahang, Selangor, Kuala Lumpur and Johor from West (Peninsular) Malaysia and Sarawak and Sabah from East (Island) Malaysia. A total of 436 stray dogs from 9 animal shelters were selected for this study comprising seven animal shelters from West Malaysia and two animal shelters from East Malaysia. Age-groups were stratified into young and adult, while the breeds were broadly classified into pedigree and local. Whole blood was collected from each dog and DNA extraction was carried out. All DNA samples were screened via standard PCR using familyspecific primers that amplify the 360bp fragment of the 16S rRNA gene for Anaplasma and Ehrlichia and a genus specific primer that amplify the 350bp fragment of the 18S rRNA gene for Babesia and Hepatozoon. Amplicons obtained were extracted, purified and confirmed by sequencing. For characterization, DNA from the purified PCR product from each representative samples were cloned into a suitable bacterial cell (Escherichia coli). Relations between categorical outcomes were compared using the chi-square test and prevalence rates were calculated at 95% confidence interval. For the characterization study, sequences were aligned and edited using the BioEdit ClustalW program. For comparing and analyzing the nucleotide sequences, the BLAST program was used. The phylogenetic trees were constructed using the Neighbor-Joining method. This study confirmed the molecular prevalence of five tick-borne hemopathogens namely: A. platys, B. vogeli, B. gibsoni, E. canis and H. canis in Malaysia with A. platys being the most prevalent hemopathogen (36.5%), followed by B. gibsoni (27.6%), B. vogeli (22.5%), E. canis (18.8%) and H. canis (15.8%). Presence of co-infection was also established with a concurrent infection with A. platys and Babesia being the most prevalent (18.8%); followed by Babesia and E. canis (10.8%), A. platys and E. canis (8.4%), H. canis and Babesia (6.4%), H. canis and E. canis (4.6%) and H. canis and A. platys (2.7%). Triple infection combination of Babesia-Anaplasma-Ehrlichia predominated (61.3%, 19 dogs). However, local breeds showed a significantly (p > 0.05) higher infection rate than the pedigree breed for H. canis, Babesia and A. platys (p= 0.03, 0.001 and 0.04 respectively). Spatial distribution based on individual pathogens per region showed that Northern East Malaysia (Sabah) had the highest prevalence for H. canis (37%); B. vogeli (35.7%) and A. platys (64.9%) predominated in West Peninsular, while B. gibsoni (76%) and E. canis (46%) predominated in Southern East Malaysia (Sarawak). Distribution of hemopathogens based on geographic locations in Malaysia revealed that Southern East Malaysia (Sarawak) had the highest prevalence for tick-borne hemopathogens in Malaysia. Infectivity status to hemopathogens among stray dogs revealed that the Eastern Peninsular predominated for infectivity with at least one hemopathogen (35.4%), while the Southern East Malaysia (Sarawak) predominated for dogs infected with 2, 3, 4, and all the 5 pathogens under investigation with prevalence of 44%, 20%, 6% and 2% respectively. This study reported for the first time the genetic diversity of tick-borne hemopathogens among stray dogs in Malaysia and indicated the presence of both indigenous and foreign genotypes in Malaysia. West Peninsular Malaysia showed the highest number of genotypes, followed by the Southern East Malaysia (Sarawak). The findings from this study provided a comprehensive data on the etiologies of canine tick-borne hemopathogens, their distribution and genetic diversities in Malaysia. This study can also be used for future epidemiological studies and or intervention programme. However, the zoonotic aspects of this hemopathogens as well as the reservoirs of infection have not been looked into in this study; thus, there is the need to further expand our knowledge on that aspect.